Risk factors of recurrent acute pancreatitis after conservative treatment in pediatric population: a single-center study - Jianghua Zhan (World Journal of Pediatric Surgery, 2021)
Background Although complete resolution and recovery occurs in most children with an initial attack of acute pancreatitis (AP), a subset of children may progress to recurrent AP (RAP). RAP has serious effects to the individual and the socioeconomic burden. The aim of this project was to identify the independent risk factors for pediatric RAP so as to provide evidence for its prevention, early diagnosis and treatment.Methods A retrospective cohort study of children discharged from Tianjin Children’s Hospital from June 2017 to January 2020 was performed. Demographic and clinical variables, treatment strategies, clinical course and outcomes were collected. Independent risk factors of RAP were identified using the logistic regression model.Results Of the total 96 enrolled children, 30 (31.3%) developed RAP during the follow-up period. The majority (27/30, 90%) of the children with AP developed RAP within 6 months of their first AP attack. The presence of systemic inflammatory response syndrome (SIRS) [odds ratio (OR)=6.652, 95% confidence interval (CI) 1.989 to 22.247], fasting time (OR=1.267, 95% CI 1.104 to 1.583), whether meet all three AP diagnostic criteria (OR=7.438, 95% CI 1.346 to 41.103) and abnormal amylase/lipase value on the seventh day of hospitalization (OR=3.601, 95% CI 0.972 to 13.342) were independent risk factors of RAP in children.Conclusions Most children who developed RAP had progressed within 6 months after their first episode of AP. RAP was more common in children who met all three AP diagnostic criteria at initial attack and in children with SIRS, long fasting time and abnormal amylase/lipase value on the seventh day of hospitalization.